2013
DOI: 10.1177/1533317513511287
|View full text |Cite
|
Sign up to set email alerts
|

Practices Used in Israel by Nurses Who Care During Hospitalization for Older Patients With Dementia or Who are Bedridden

Abstract: The study's purpose was to examine (a) bedside nurses' care practices when providing care to patients with dementia or those who are physically disabled and (b) the extent to which these actions vary by type of hospital, type of ward, and nurse's characteristics. The sample included 265 nurses in internal medicine and geriatric wards in 2 general hospitals in Israel. The results showed that the most prevalent practices were giving greater attention to these patients, locating them in a room near the nurses' st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…A more recent study, regarding nursing students in Israel, revealed that, in comparison with their Israeli-Jewish counterparts, Arab nursing students are more willing to take care of older adults in need of care (Zisberg, Topaz and Band-Wintershtein 2015). Finally, another interesting study, with respect to hospital nurses caring for older adults who were bedridden, revealed that Israeli-Jewish nurses who immigrated from the former Soviet Union reported using more physical restraints than other Israeli-Jewish nurses (Iecovich and Rabin 2013). Hence, nurses who immigrated from the former Soviet Union were less concerned with respecting the autonomy of these older adults, entailed in acknowledging their humanness.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study, regarding nursing students in Israel, revealed that, in comparison with their Israeli-Jewish counterparts, Arab nursing students are more willing to take care of older adults in need of care (Zisberg, Topaz and Band-Wintershtein 2015). Finally, another interesting study, with respect to hospital nurses caring for older adults who were bedridden, revealed that Israeli-Jewish nurses who immigrated from the former Soviet Union reported using more physical restraints than other Israeli-Jewish nurses (Iecovich and Rabin 2013). Hence, nurses who immigrated from the former Soviet Union were less concerned with respecting the autonomy of these older adults, entailed in acknowledging their humanness.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study, regarding nursing students in Israel, revealed that Arab nursing students are more willing to take care of older people, in comparison with their Israeli Jews counterparts (Zisberg, Topaz, & Band-Wintershtein, 2015). Another interesting study, with respect to hospital nurses caring for older adults who were bedridden, found that nurses who immigrated from the former Soviet Union reported using more physical restraints than other Israeli Jewish nurses (Iecovich & Rabin, 2013). Hence, nurses who immigrated from the former Soviet Union were apparently less concerned with respecting the autonomy of these older people, entailed in acknowledging their humanness.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Israeli nurses born in the former Soviet Union reported using more physical restraints than other Israeli-Jewish nurses. 18 However, most of these studies' explorations regarding the conceptualization of autonomy by varied cultural groups in the context of caring for older persons in long-term care facilities are detached from perceptions of human dignity. Arguably, in philosophical discourse, varied possible meanings have been attributed to the concept of ''dignity,'' and discussing them here is well beyond the scope of the current article.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Israeli nurses born in the former Soviet Union reported using more physical restraints than other Israeli-Jewish nurses. 18…”
Section: Introductionmentioning
confidence: 99%